Scholarly activity as a selection criterion in the Canadian Residency Matching Service (CaRMS): A review of published criteria by internal medicine, family medicine, and pediatrics programs - Lukings, Jorin; Bell, Amanda; Stobbe, Karl; Basha, Vesa; Brazier, Jessie; Dragomir, Delia; Glibbery, Meghan; Kearney, Hannah; Knapp, Alison; Levin, Daniel; et al. (Canadian Medical Education Journal, 2020)
Background: Undergraduate medical students seek as much information as possible as to how residency programs select candidates. The Canadian Residency Matching Service (CaRMS) website is one of their primary sources of information. Students may be more competitive in the match if they know whether scholarly activity is used in the selection process by their preferred programs, as described on the CaRMS website.. Methods: For all 17 Canadian faculties of medicine, 2019 R1 entry internal medicine, family medicine and pediatrics program descriptions were reviewed on the CaRMS website looking for keywords related to scholarly activity. Results: Forty-one percent of family medicine, 65% of internal medicine and 71% of pediatric programs explicitly stated having interest in applicants with scholarly experience. In Western Canada, 80% of internal medicine and 60% of pediatrics programs included scholarly activity in their CaRMS description of criteria considered in ranking applications. Similarly, in Ontario, 66% of internal medicine and 83% of pediatrics programs mentioned scholarly activity as a valuable quality. In Quebec 100% of family medicine and 50% of pediatrics programs include scholarly activity in their descriptions. Pediatrics and internal medicine programs (100%) in Atlantic Canada mentioned scholarly activities but neither of the two Atlantic Canada internal medicine programs mentioned scholarly activities. Conclusion: Undergraduate medical students can use this project to prioritize extracurricular activities and scholarly work to be competitive for application to family medicine, internal medicine and pediatrics residency programs.